INDEKS KEPUASAN MASYARAKAT SPESIFIK LEMBAGA PENELITIAN DAN PENGEMBANGAN: IMPLEMENTASI MODEL ACSI (THE COMMUNITY SATISFACTION INDEX ON SPECIFICLY RESEARCH AND DEVELOPMENT: IMPLEMENTATION OF ACSI MODEL) - dan Prakoso Bhairawa Putera, Budi Triyono (Jurnal Borneo Administrator, 2013)
Law number 25 year 2009 concerning Public Service highlights one important thing about Community Satisfaction Index (CSI). CSI becomes an important aspect to see the extent to which Unit of Organization is able to provide excellent service. CSI measurement is generally refer to the Ministry of Administrative Reform Decision Number KEP/25/M.PAN/2/2004 concerning General Guidelines to Measure Community Satisfaction Index. However, the measurement is felt less suitable for research institute organizations and development (R & D). Institute for R & D organization has specific characteristics that require measurement-oriented SMEs such specificity. This paper provides a concept of development of SMEs is more suitable measurement implemented for R & D institutions in Indonesia. The concept is oriented towards the development of measurement products and services R & D, product and service performance of R & D services, the performance of the delivery staff, accessibility, communication, satisfaction with services R & D products and services, the impact of satisfaction, and improved services.Keywords: SMEs, Public Service, Institute for Research and Development, ReformsUndang-undang No. 25 Tahun 2009 tentang Pelayanan Publik menggaris bawahi salah satu hal penting mengenai Indeks Kepuasan Masyarakat (IKM). Keberdaan IKM menjadi penting untuk melihat sejauh mana unit organisasi mampu memberikan pelayanan prima. Pengukuran IKM yang umumnya digunakan merujuk pada KEP/25/M.PAN/2/2004 tentang Pedoman Umum Penyusunan Indeks Kepuasan Masyarakat. Pengukuran tersebut dirasakan kurang cocok digunakan untuk lembaga organisasi penelitian dan pengembangan (litbang). Lembaga Organisasi litbang memiliki karakteristik khusus sehingga membutuhkan pengukuran IKM yang berorientasi pada kekhususan tersebut. Makalah ini memberikan konsep pengembangan pengukuran IKM yang lebih cocok diimplementasikan bagi lembaga litbang di Indonesia. Konsep pengembangan pengukuran ini berorientasi pada penggunaan produk dan jasa litbang, kinerja layanan produk dan jasa litbang, kinerja staf penyelenggaran, aksesibilitas, komunikasi, kepuasan terhadap layanan produk dan jasa litbang, dampak kepuasan, dan perbaikan layanan.Kata kunci: IKM, Pelayanan Publik, Lembaga Litbang, Reformasi